Current state of the health care system of Karaganda region - Aimagambetov, E.B.; Tyngisheva , А.М. (BUKETOV BUSINESS REVIEW, 2019)
Public health is substantially dependent on the functioning of the health care system, ensuring the highest possible availability and quality of medical care. The article discusses the state and trends in the development of a health care system of Karaganda region. The health care of Karaganda region is a socially-oriented system designed to ensure the availability, timeliness, quality and continuity of the provision of medical care to population. Today, the main strategic goal of the health care of Karaganda region is to strengthen health of the population in order to ensure sustainable socio-economic development of the country. The authors carried out a theoretical review of organization of the health care system. A comparative analysis of the main health indicators of Karaganda region, namely the infrastructure of the health system, the state of staffing, medical and demographic indicators, etc., was conducted. Based on the analysis, the main features of functioning of the health care system of Karaganda region are identified. The authors paid special attention to key areas of a health care system reform in Karaganda region. For solving the objectives posed the authors used statistical techniques (data collection, analysis and comparison) as methods of research. Thus, a comparative analysis of indicators of the health care system of Karaganda region reveals the existing problems and proposes ways to solve them, taking into account the implementation of the main measures of the health care modernization program on improvement of information technologies, development of public-private partnerships in order to justify and develop an effective mechanism for managing the health care system.